The Role of Biosimilars in Uveitis: Long-Term Real-World Outcomes of the Switch From Original to Biosimilar TNF-Alpha Inhibitors - Fabiani, Claudia; Vitale, Antonio; Emmi, Giacomo; Sgheri, Arianna; Lopalco, Giuseppe; Sota, Jurgen; Guerriero, Silvana; Iannone, Florenzo; Frediani, Bruno; Vannozzi, Lorenzo; Bianco, Maria Teresa; Giovannini, Valtere; et al. (Frontiers in Pharmacology, 2019)
Background: recent expiry of patents for tumor necrosis factor(TNF)-α inhibitors has led to the employment of biosimilars in clinical practice. The aim of the study was to identify any change in the control of ocular inflammatory manifestations among patients with non-infectious uveitis switching from an originator to a corresponding anti-TNF-α biosimilar. Methods: 37 consecutive patients (62 eyes involved) with non-infectious uveitis undergoing the switch from anti-TNF-α originators to biosimilars were retrospectively enrolled; the frequency of ocular flares before and after the switch as well as best corrected visual acuity (BCVA), central macular thickness (CMT), daily systemic corticosteroid intake, and frequency of uveitic macular edema (UME) at the switch and at the following assessments were statistically analysed. Results: the number of ocular flares during the 12 months preceding the switch was 16, corresponding to 3.6 flares/100 patients/12 months; the number of flares after the switch was 14, corresponding to 2.0 flares/100 patients/12 months. No statistically significant differences were identified in the frequency of flares (p=0.84) and in the number of patients experiencing ocular flares (p=0.39) between the twelve months preceding the switch and the period thereafter. No statistically significant changes were observed in the BCVA (p=0.27), CMT (p=0.50), frequency of UME (p=0.57) and daily corticosteroid intake (p=0.42) between the time of the switch and the last follow-up visit. Conclusions: the switch to biosimilars represents a feasible treatment choice associated with the maintenance of clinical efficacy in patients with non-infectious uveitis previously treated with the corresponding originator anti-TNF-α biologic agents.